The Collaborative Governance Handling Election Violations In The 2024 Cirebon City Election - Fadilah, Rifa Amrizal; Hidayat, Moh. Taufik (ann4publisher@gmail.com, 2025)
Background. The election of Regional Heads (Pilkada) in a democracy is one of the main pillars that must be carried out in a transparent and accountable manner. However, in reality, there are still many violations that occur in this democratic process, such as money politics, campaigns that are not on schedule, and abuse of authority, which remain problems and challenges in the 2024 Cirebon City Regional Elections. Aims. The purpose of this problem is to analyze how the application of the collaborative governance model can serve as a solution to overcoming various violations that occur during the election process, especially in the context of the Cirebon City Regional Elections. The solution to this problem is to research the application of collaborative governance in handling election violations. This Collaborative governance model focuses on cooperation between BAWASLU (Election Supervisory Agency) and KPU (General Election Commission), as well as other actors, in organizing elections. Methods. The research method used was qualitative descriptive, with data collection techniques through interviews. Result. The results of his research are that the success of collaborative governance depends on strong coordination between institutions, transparent supervision, and increased trust in the electoral process from public participation. However, the obstacles faced are still weak rules and regulations, limited resources, and resistance from political actors. Conclusion. This research also provides a way in collaborative governance to minimize election violations, with the goal that the collaborative governance model can be an effective solution in creating good and clean elections and reducing election violations.